Ultrasound-assisted periconal ocular blockade in rabbits - Najman, Ilana E. [UNESP]; Ferreira, Joana Z. [UNESP]; Abimussi, Caio J. X. [UNESP]; Floriano, Beatriz P. [UNESP]; Meneghetti, Thais M. [UNESP]; Oliva, Valeria N. L. S. [UNESP]; Nascimento, Paulo do [UNESP] (Wiley-Blackwell, 2015)
ObjectiveThis study aimed to evaluate the benefit and specifically the feasibility of using ultrasound in ophthalmologic periconal block, and the occurrence of complications.Study designProspective experimental study.AnimalsTen healthy New Zealand White rabbits (6-8months of age), weighing 2.0-3.5kg.MethodsRabbits were anesthetized by intramuscular injection of acepromazine (1mgkg(-1)), ketamine (30mgkg(-1)) and xylazine (3mgkg(-1)). Ultrasound-assisted periconal block with lidocaine was performed on 18 eyes. Intraocular pressure was measured by applanation tonometry whereas corneal sensitivity was assessed using an esthesiometer, before and after each periconal anesthesia.ResultsIn all 18 eyes, it was possible to adequately visualize the needle shaft within the periconal space, as well as muscular cone, optic nerve and local anesthetic solution spread. Lidocaine 2% without epinephrine (0.790.19mL) was injected into the periconal space. There was no statistical difference between the intraocular pressure (meanSD) measured before (10.9 +/- 2.9mmHg) and after (11.9 +/- 3.8mmHg) the periconal anesthesia (p=0.38). The effectiveness of the ultrasound-assisted technique was shown according to the values for corneal sensitivity, assessed before and after periconal anesthesia (p<0.0001). Complications were not observed in this study.ConclusionsEye ultrasonography allowed visualization of all anatomic structures necessary to perform a periconal block, as well as the needle insertion and anesthetic spread in real time. Further studies are required to prove the real potential of ultrasound for reducing the incidence of complications associated with ophthalmic blocks, especially when anatomic disorders of the eye could potentially increase the risk.Clinical relevanceUltrasonography is a painless, noninvasive tool that may improve safety of ophthalmic regional blocks, potentially by reducing the prevalence of globe perforation or penetration of the optic nerve associated with the needle-based techniques.
Keywords: Anesthesia; Eye; Periconal blockade; Rabbits; Ultrasound